Environment, Social, and Governance Performance and Firm’s Equity Liquidity: Evidence from Emerging Markets - Ho Thi Hai , Ly (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
This study examines the impact of corporate social responsibility on stock liquidity. Using panel data of 159 companies from emerging markets for the period 2002–2016, the study shows that firms operating in emerging markets with higher levels of social responsibility will have lower stock liquidity. This negative relationship comes from all three aspects of corporate social responsibility including environmental, social, and governance indicators. This result is consistent with the hypothesis that in emerging markets, information manipulation and a lower level of investor protection cause information asymmetry. As a result, investing in corporate social responsibility activities is often viewed as non-transparent, and can even exacerbate asymmetric information. Furthermore, the negative relationship between corporate social responsibility and stock liquidity is weakened for firms audited by leading reputable auditors or firms operating in better institutional environments.
Keywords: Corporate social responsibility; Stock liquidity; Big5; Institutional environments